Minecraft - Mojang AB (Firm) (Redmond, Washington Microsoft Corporation, 2014)
Experience the Minecraft gaming phenomenon, rebuilt with new features designed for Xbox One. Create worlds limited only by your imagination. Explore, build, and conquer alone or with your friends via split-screen mode or over Xbox LIVE. Minecraft for Xbox One lets you create worlds from the comfort of your sofa. Play alone or play with your friends. At night monsters come out, so make sure to build a shelter before that happens. After that, your world is your imagination.
1-4 players, co-op 2-4.
44Z-00005.
Rating: PG.
System requirements: For use only with Xbox One system.
105190
Keywords: Mining engineering -- Computer games; Building -- Computer games; Video games; Computer games